Environmental education policy support in Southern Africa: a case story of SADC REEP - Gumede, Sibusisiwe Marie-Louise (Rhodes University, Faculty of Education, Department of Education, 2009)
The study takes place in the context of the Southern African Development Community's Regional Environmental Education Programme (SADC REEP). The SADC REEP is a programme of the Food Agriculture and Natural Resources Directorate of the SADC Secretariat. The programme is implemented through four components namely policy, networking, training and learning support materials development. The bulk of the policy budget is in the form of seed funding to support policy initiatives in the member states. The intention of this study is to illuminate factors that influence the deployment and use of seed funding to support environmental education policy processes within the SADC REEP. To sharpen the understanding of the context within which these activities take place, the study looks at the global and regional landscape of policy events and their influence on policy in the sub-region. The study also looks at the landscape of the fields within which environmental education is embedded, the power relations, and the notion of agency in environmental education policy processes. The discourse in environmental education policy processes is analyzed by drawing on Bourdieu's constructivist structuralism to highlight some of the social and institutional complexities in dynamic fields, capital and policy context. The research takes a qualitative interpretative approach using case study methodology to explore the processes and influences that have a bearing on the SADC REEP policy sub-component, specifically the deployment and use of seed funding for policy initiatives. The findings show the complexity of the variables at play in shaping the processes of developing and reviewing environmental education policies in the sub-region. These variables include discourse that is used, economics and politics of the responsible institutions and actors, as well as relationships between the environmental field and education field. The results point towards a need to clearly understand the policy context within which the SADC REEP is operating in order to make correct assumptions, to develop realist expectations, and to put in place appropriate mechanisms that will effect the expectations. The study recommends further probing of the relationship between the actors and networks in relation to the success of policy processes. It also recommends a further exploration of the SADC REEP's open-ended approach with respect to articulating the monitoring and consolidation of the successes in supporting environmental education policy processes.
Keywords: SADC Regional Environmental Education Programme; Environmental education -- Africa, Southern; Education -- Africa, Southern; Education and state -- Africa, Southern; Teaching -- Aids and devices -- Africa, Southern